ANALISIS KETERAMPILAN MENULIS LAPORAN PENELITIAN TINDAKAN KELAS GURU SEKOLAH DASAR - Siti Halidjah (JURNAL PENDIDIKAN DASAR, 2023)
Abstract: This study aims to describe the results of the analysis of writing skills of class action research reports of elementary school teachers.  Theproximity used is a qualitative approach with a descriptive method.  The subject of the study was elementary school teachers who participated in technical guidance activities for scientific papers.   The source of the data is in the form of documents from research reports.  The research procedure is carried out with the stages of planning, implementing, analyzing data, and reporting. The documentation study technique is selected in this research with the tool in the form of a work document.  Data analysis is carried out by steps of collection, reduction, presentation, and inference. The results showed that the skills of writing class action research reports for elementary school teachers were very good with the presesntase of achievement. This can be seen from the result data, namely 50.00% (7 teachers) obtained scores in the range of 81-100, 35.71% (5 teachers) obtained scores in the range of 61-80, and only 14.29 (1 teacher) obtained scores in the range of 41-60. Keywords:  writing skills, classroom action research Abstrak: Penelitian ini bertujuan untuk mendeksipsikan hasil analisis keterampilan menulis laporan penelitian tindakan kelas guru sekolah dasar. Pendekatan yang digunakan adalah pendekatan kualitatif dengan metode deskriptif. Subjek penelitian yaitu guru sekolah dasar peserta kegiatan bimbingan teknis karya tulis ilmiah. Sumber data berupa dokumen hasil laporan penelitian. Prosedur penelitian dilakukan dengan tahapan perencanaan, pelaksanaan, analisis data, dan pelaporan. Teknik studi dokumentasi dipilih dalam penelitina ini dengan alatnya berupa dokumen hasil kerja. Analisis data dilakukan dengan langkah pengumpulan, reduksi, penyajian, dan penyimpulan. Hasil penelitian menunjukkan bahwa keterampilan menulis laporan penelitian tindakan kelas guru sekolah dasar tergolong baik sekali dengan presesntase ketercapaian. Hal ini terlihat dari data hasil yaitu 50,00% (7 guru) memperoleh nilai di rentang 81—100, 35,71% (5 guru) memperoleh nilai di rentang 61—80, dan hanya 14,29 (1 guru) yang memperoleh nilai di rentang 41—60. Kata Kunci: keterampilan menulis, penelitian tindakan kelas